Food insecurity confrontation by pastoralist and agrarian communities in South Omo Zone, Ethiopia: a facility-based qualitative study - Mintesinot Melka Gujo; Lebitsi Maud Modiba (Journal of Nutritional Science)
Food insecurity remains a global issue, particularly in developing countries like Ethiopia. Thus, this study focused on identifying factors contributing to food insecurity and the strategies used to cope with it among agrarian and pastoralist communities of South Ari and Benatsemay Woreda, respectively. A facility-based qualitative study was carried out in Southern Ethiopia. Participants were selected using a purposefully targeting health extension workers, health centre directors, woreda programme experts, district health managers, and pregnant women staying in maternity waiting homes. The selection process included one health facility from each district, focusing on those with the highest number of pregnant women in maternity waiting homes. A total of 17 participants were involved in in-depth interviews, and 2 focus group discussions were conducted with 27 pregnant women, continuing until data saturation was achieved. Field notes were taken, and sessions were voice recorded. Participants in both in-depth interviews and focus group discussions frequently identified several causes of food insecurity in the community, such as food shortages, climate change, rising prices of agricultural products, inadequate agricultural technology, scarcity of farmland, and income constraints. Tailored intervention is highly demanding to implement policies to stabilise food supply chains and mitigate food shortages in both agrarian and pastoralist areas, invest in modern agricultural technologies to boost productivity, encourage the adoption of climate-smart agricultural practices to help farmers adapt to changing weather patterns, optimise the productive use of available farmland, promote income-generating activities, and diversify livelihoods to alleviate income constraints and improve food security.